Factors Affecting Adoption of Maize Varieties in Nepal - Upadhyay, N.; Ghimire, Y. N.; Sharma, B.; Acharya, Y.; Gairhe, S.; Sapkota, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
This study examined status of adoption of improved maize varieties in Nepal. Six hundred eighty two households were sampled from six districts namely Sindhupalchowk, Lalitpur, Khotang, Dang, Chitwan and Dadeldhura. Data was analyzed through descriptive statistics. The results indicated that the slow growth rate of area, production and yield was around 2.7% p.a. and growth rate is moreover stagnant rate from 1990-2015. Adoption of modern variety was found to be 75% of household. Mean area of maize cultivation in Nepal is 0.431 ha/HH. Only seven improved variety were adopted in large scale and they were adopted in 70.60% of maize cultivating areas. Improved variety Rampur composite, Mankamana-3 and Deuti and Hybrid CP 808 were found to be highly adopted. While CP 808, Shrestha and Rajkumar hybrids were dominating hybrids. Age of household head, Caste, Migration, credit accessibility, cooperative involvement, extension visit, training, formal sector seed availability and knowledge about agricultural insurance were found positive factors affecting adoption of modern variety of maize. However education and livestock numbers found negatively contribute to adoption.